Investigation of the radiation parameters of an oscillating charge in an ion system - Shulaev Nikolay; Efimova Galina (EPJ Web of Conferences)
A solution to the problem of determining the frequency spectrum and intensity of electromagnetic radiation generated by an oscillating charge in a dipole-quadrupole system has been obtained. The analysis of the obtained dependences for the oscillation frequencies reveals that knowing the maximum and minimum frequencies of the oscillating charge radiation spectrum allows for the calculation of molecular parameters. This analysis can be applied to study the electromagnetic radiation spectra of atoms and molecules in an excited state, as well as the parameters of the crystal lattice.